In vitro estimation of fast and slow wave parameters of thin trabecular bone using space-alternating generalized expectation–maximization algorithm - Grimes, Morad; Bouhadjera, Abdelmalek; Haddad, Sofiane; Benkedidah, Toufik (Ultrasonics, 2012)
► The wave propagation in thin trabecular bone is performed using Biot’s FDTD method. ► The Biot’s fast and slow waves are superimposed. ► The SAGE algorithm was used as a new approach for slow and fast waves separation. In testing cancellous bone using ultrasound, two types of longitudinal Biot’s waves are observed in the received signal. These are known as fast and slow waves and their appearance depend on the alignment of bone trabeculae in the propagation path and the thickness of the specimen under test (SUT). They can be used as an effective tool for the diagnosis of osteoporosis because wave propagation behavior depends on the bone structure. However, the identification of these waves in the received signal can be difficult to achieve. In this study, ultrasonic wave propagation in a 4mm thick bovine cancellous bone in the direction parallel to the trabecular alignment is considered. The observed Biot’s fast and slow longitudinal waves are superimposed; which makes it difficult to extract any information from the received signal. These two waves can be separated using the space alternating generalized expectation maximization (SAGE) algorithm. The latter has been used mainly in speech processing. In this new approach, parameters such as, arrival time, center frequency, bandwidth, amplitude, phase and velocity of each wave are estimated. The B-Scan images and its associated A-scans obtained through simulations using Biot’s finite-difference time-domain (FDTD) method are validated experimentally using a thin bone sample obtained from the femoral-head of a 30months old bovine.